Borderline personality disorder and violence in the UK population: categorical and dimensional trait assessment. Issue 1 (December 2016) - González, Rafael; Igoumenou, Artemis; Kallis, Constantinos; Coid, Jeremy
Abstract Background Borderline personality disorder (BPD) is characterised by difficulties with impulse control and affective dysregulation. It is unclear whether BPD contributes to the perpetration of violence or whether this is explained by comorbidity. We explored independent associations between categorical and dimensional representations of BPD and violence in the general population, and differential associations from individual BPD criteria. Methods We used a representative combined sample of 14, 753 men and women from two British national surveys of adults (≥16 years). BPD was assessed using the Structured Clinical Interview II- Questionnaire. We measured self-reported violent behaviour in the past 5 years, including severity, victims and locations of incidents. Associations for binary, dimensional and trait-level exposures were performed using weighted logistic regression, adjusted for demography and comorbid psychopathology. Results Categorical diagnosis of BPD was associated only with intimate partner violence (IPV). Associations with serious violence leading to injuries and repetitive violence were better explained by comorbid substance misuse, anxiety and antisocial personality disorder (ASPD). However, anger andimpulsivity BPD items were independently associated with most violent outcomes including severity, repetition and injury;suicidal behaviours andaffective instability were not associated with violence. Both trait-level and severity-dimensional analyses showed that BPD symptoms might impact males and females differently in terms of violence. Conclusions For individuals diagnosed BPD, violence is better explained by comorbidity. However, BPD individual traits show different pathways to violence at the population level. Gender differences in BPD traits and their severity indicate distinct, underlying mechanisms towards violence. BPD and traits should be evaluated in perpetrators of IPV.